The comparison of premature ejaculation assessment questionnaires in four premature ejaculation syndromes: Results from the Turkish Society of Andrology Sexual Health Survey - Serefoglu, E. C.; Yaman, O.; Cayan, S.; Asci, R.; Orhan, I; Usta, M. F.; Kadioglu, A. (Wiley-Blackwell Publishing, Inc, 2010)
[Abstract Not Available]